Post-traumatic Stress Disorder Symptoms and Its Predictors Among Healthcare Workers Following COVID-19 Pandemic in Southern Ethiopia: A Cross-Sectional Study - Ayalew, Mohammed; Deribe, Bedilu; Abraham, Yacob; Reta, Yared; Tadesse, Fikru; Defar, Semira (Frontiers in Psychiatry, 2022)
Background: COVID-19 causes immense psychological pressure on communities in addition to physical misery. There is currently a scarcity of data on the psychological impact of the COVID-19 epidemic on Ethiopian healthcare workers (HCWs). Therefore, this study was aimed to assess the post-traumatic stress disorder (PTSD) symptoms and its predictors following COVID-19 pandemic among healthcare workers (HCWs) in southern Ethiopia. Methods: A hospital based cross-sectional study design was used among 387 randomly selected HCWs between September 25 and October 25, 2020 at four selected public hospitals in Sidama National Regional State, southern Ethiopia. Impact of Event Scale-Revised (IES-R) was used to collect data post-traumatic stress disorder (PTSD) symptoms. Logistic regression analyses with 95% CI were used to examine the relationship between independent and outcome variables. Result: The prevalence of PTSD symptoms was found in 56.8% of participants. Significant factors that increase risk of PTSD symptoms were being female (AOR = 1.91, 95% CI = 1.19, 3.05), married (AOR = 1.87, 95% CI = 1.12, 3.14) and nurses (AOR = 3.31, 95% CI = 1.66, 6.63). On the other hand, HCWs working other than emergency unit such as inpatients/wards (AOR = 0.43, 95% CI = 0.24, 0.75), OPD (AOR = 0.48, 95% CI = 0.24, 0.97) and other units (AOR = 0.49, 95% CI = 0.25, 0.96) less likely to be affected by PTSD symptoms. Conclusion: The current study showed high levels of PTSD symptoms as psychological challenges for HCWs. Sex, age, marital status, type of profession and working environment were significant factors for PTSD symptoms in HCWs during the pandemic. HCWs require mental health support during and after the pandemic.